Sex and gender differences in acute stroke care: metrics, access to treatment and outcome. A territorial analysis of the Stroke Code System of Catalonia. (June 2023) - Silva, Yolanda; Sánchez-Cirera, Laura; Terceño, Mikel; Dorado, Laura; Valls, Adrián; Martínez, Marina; Abilleira, Sònia; Rubiera, Marta; Quesada, Helena; Llull, Laura; Rodríguez-Campello, Ana; Martí-Fàbregas, Joan; et al.
Introduction: Previous studies have reported differences in the management and outcome of women stroke patients in comparison with men. We aim to analyze sex and gender differences in the medical assistance, access to treatment and outcome of acute stroke patients in Catalonia. Patients and methods: Data were obtained from a prospective population-based registry of stroke code activations in Catalonia (CICAT) from January/2016 to December/2019. The registry includes demographic data, stroke severity, stroke subtype, reperfusion therapy, and time workflow. Centralized clinical outcome at 90 days was assessed in patients receiving reperfusion therapy. Results: A total of 23, 371 stroke code activations were registered (54% men, 46% women). No differences in prehospital time metrics were observed. Women more frequently had a final diagnosis of stroke mimic, were older and had a previous worse functional situation. Among ischemic stroke patients, women had higher stroke severity and more frequently presented proximal large vessel occlusion. Women received more frequently reperfusion therapy (48.2% vs 43.1%, p  < 0.001). Women tended to present a worse outcome at 90 days, especially for the group receiving only IVT (good outcome 56.7% vs 63.8%; p  < 0.001), but not for the group of patients treated with IVT + MT or MT alone, although sex was not independently associated with clinical outcome in logistic regression analysis (OR 1.07; 95% CI, 0.94–1.23; p  = 0.27) nor in the analysis after matching using the propensity score (OR 1.09; 95% CI, 0.97–1.22). Discussion and conclusion: We found some differences by sex in that acute stroke was more frequent in older women and the stroke severity was higher. We found no differences in medical assistance times, access to reperfusion treatment and early complications. Worse clinical outcome at 90 days in women was conditioned by stroke severity and older age, but not by sex itself.